A biographical approach to personal evaluation of the high and low achieving seniors of the Ramon Magsaysay High School - Wee Sit, Josefina (Abaya) 1934- (s.n.], 1966)
This study was undertaken to demonstrate the use of the biographical approach to personal evaluation of a group of senior high school students who have shown high and low academic achievement in the third year and to shed light to the assumption that student academic achievement is related to biographical factors.